M Protein-Deficient Respiratory Syncytial Virus (RSV) Vaccine Protects Infant Baboons Against RSV Challenge. (4th October 2017) - Welliver, Robert C; Oomens, Antonius; Wolf, Roman; Papin, James; Ivanov, Vadim; Preno, Alisha; Staats, Rachel; Piedra, Pedro; Yu, Zhongxin
Abstract: Background: RSV bronchiolitis is the most common cause of hospitalization of infants in the US, and may lead to the development of long-term airway disease. Inactivated vaccines may lead to enhanced disease, while replicating vaccines have caused unacceptable degrees of illness, and may revert back to wild type. We developed an RSV vaccine lacking the gene for the M protein (Mnull RSV). The M protein is responsible for reassembly of the virus after it infects cells and expresses its proteins. Infant baboons vaccinated intranasally (IN) with Mnull RSV develop serum neutralizing antibody (NA) responses, but the virus does not replicate. Methods: 2-week-old baboons ( n  = 12) were primed IN with 10 7 vaccine units of Mnull RSV or a control preparation, and a similar booster dose was given 4 weeks later. Mnull RSV vaccination did not cause tachypnea, airway inflammation or other signs of illness when compared with sham-vaccinated controls. Two weeks after boosting, all infants were challenged intratracheally with human RSV A2. We continuously monitored respiratory rates and levels of overall activity. On various days following challenge, we obtained BAL fluids for leukocyte counts and degree of virus replication, and evaluated alveolar-arterial oxygen gradients (A-a O2). Results: Vaccinated animals (vs. unvaccinated controls) had lower respiratory rates ( P  = 0.0014), improved A-a O2 ( P  = 0.0063) and reduced viral replication ( P  = 0.0014). Activity scores were higher in vaccine recipients than in unvaccinated animals. Vaccine recipients also were primed for earlier serum and secretory neutralizing antibody responses, and greater airway lymphocyte responses. Airway lymphocyte numbers (but not antibody responses) were associated with lower respiratory rates and reduced viral replication ( P < 0.01). Conclusion: Vaccination intranasally with Mnull RSV protected infant baboons against an RSV challenge without causing respiratory disease or enhanced illness, and is a promising candidate for use in human infants. Lymphocyte responses to vaccination may play an equal or greater role in protection against RSV infection than antibody responses. Disclosures: All authors: No reported disclosures.